MicroRNAs as New Characters in the Plot between Epigenetics and Prostate Cancer - Paone, Alessio; Galli, Roberta; Fabbri, Muller (Frontiers in Genetics, 2011)
Prostate cancer (PCA) still represents a leading cause of death. An increasing number of studies have documented that microRNAs (miRNAs), a subgroup of non-coding RNAs with gene regulatory functions, are differentially expressed in PCA respect to the normal tissue counterpart, suggesting their involvement in prostate carcinogenesis and dissemination. Interestingly, it has been shown that miRNAs undergo the same regulatory mechanisms than any other protein coding gene, including epigenetic regulation. In turn, miRNAs can also affect the expression of oncogenes and tumor suppressor genes by targeting effectors of the epigenetic machinery, therefore indirectly affecting the epigenetic controls on these genes. Among the genes that undergo this complex regulation, there is the androgen receptor (AR), a key therapeutic target for PCA. This review will focus on the role of epigenetically regulated and epigenetically regulating miRNAs in prostate cancer and on the fine regulation of AR expression, as mediated by this miRNA-epigenetics interaction.